Cancer Metastasis : Biologic Basis and Therapeutics - Lyden, David; Welch, Danny R.; Psaila, Bethan (Cambridge : Cambridge University Press, 2011)
Metastasis is responsible for a large burden of morbidity and mortality among cancer patients, and currently few therapies specifically target metastatic disease. Further scientific dissection of the underlying pathways is required to pave the way for new therapeutic targets. This groundbreaking new text comprehensively covers the processes underlying cancer metastasis and the clinical treatment of metastatic disease. Whereas previous volumes have been compendia of laboratory research articles, the internationally renowned authors of this volume have summarized the state-of-the-art research in the metastasis field. A major section covers the cellular and molecular pathways of metastasis and experimental techniques and the systems and models applied in this field. Subsequently, the clinical aspects of the major cancer types are considered, focusing on disease-specific research and therapeutic approaches to metastatic disease. The focus is on novel pathophysiological insights and emerging therapies; future directions for research and unmet clinical needs are also discussed.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).